Determinación de parámetros tecnológicos óptimos para la obtención de un licor destilado de uva (vitis labrusca), macerado en madera estoraque ( myroxylom balsamun) - Fachin Ruiz, David (2013)
This study aimed to obtain a liquor distilled from grape (Vitis latirusca) macerated wood storax (Myroxylon balsamum). Black Burgundy grape variety, grown in the districts of San Antonio de Cumbaza and Tarapoto in San Martín province, is a variety that has low soluble solids content, high acidity, good flavor and color. Storax wood extracted from the province of Juanjui, has good color and pleasant aroma characteristic, similar to oak. The study comprised 3 stages, in the first stage is sought to determine the best conditions of treatment of wood, which was evaluated for the temperature (80 - 160 º C) and the drying time (1 - 3.horas). The second step was to determine the best conditions of extraction of timbe'r, where the best mass ratio of wood and grape liquor at 58 º were alcoholic (30, 50, 70 and 90 g I L), in arder removing substances which give flavor, color and odor of liquor and allowed to macerate for 30 days. The third stage involved the dilution of the extract obtained in the second stage, grape distillate 40 º alcoholics, dilutions were 1 O, 15, 20, 25 and 30% (v I v). puring the aging time the liquor is sensory tested by affective test (method of hedonic scale of 5 points); we used a completely randomized design with factorial arrangement, 2 levels, 4 factors with 8 axial points, 5 points more central making a total of 29 experiments. The results were, for drying timber at 120 ºe for 2 hours with 50g I L of extract chip and 20% v / v dilution, analyzing the physical characteristics - chemistry of the final product. 2